Familial cognitive deficits in schizophrenia. - Hoff, A; Svetina, C; Maurizio, A; Crow, T; Spokes, K; DeLisi, L (2005)
Susceptibility to schizophrenia is considered familial, but the mechanism for transmission has not been found. Since widespread cognitive deficits have been found in patients with schizophrenia, several of these have been proposed as candidate familial endophenotypes that may or may not be predictive of who develops the illness. The current study examines these candidates in individuals from 32 families with at least 2 members having the diagnosis of chronic schizophrenia and normal comparison subjects using an extensive neuropsychological battery. Consistent with previous literature, family members with schizophrenia were significantly impaired on all measures compared with controls. Well relatives demonstrated significantly worse performance on a measure of verbal learning, delayed visual recall, perceptual-motor, and pure motor speed. Expressive and receptive language, but not other functions, were highly correlated within both concordant for schizophrenia and discordant sibling pairs, suggesting that they are familial vulnerability endophenotypes, but not predictive of whom becomes ill. On the other hand, some measures of perceptual-motor, pure motor speed, and frontal/executive functioning were significantly correlated in concordant, but not discordant pairs. These latter correlations suggest that some cognitive measures may be genetically related to the illness.